2016
DOI: 10.1007/s12561-016-9170-z
|View full text |Cite
|
Sign up to set email alerts
|

A LASSO Method to Identify Protein Signature Predicting Post-transplant Renal Graft Survival

Abstract: Identifying novel biomarkers to predict renal graft survival is important in post-transplant clinical practice. Serum creatinine, currently the most popular surrogate biomarker, offers limited information of the underlying allograft profiles. It is known to perform unsatisfactorily to predict renal function. In this paper, we apply a LASSO machine-learning algorithm in the Cox proportional hazards model to identify promising proteins that are associated with the hazard of allograft loss after renal transplanta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 50 publications
0
7
0
1
Order By: Relevance
“…Lasso has two important characteristics, one is feature selection: automatic selection of features, it will learn to remove features without information and precisely set the weights of these features to zero, especially for high-dimensional data. Another one is interpretability: models are easier to explain, for example, we can find the independent variables that provide the most important information in the model when we have a lot of independent variables [2326]. Li et al identified 13 differentially expressed miRNAs in the serum of HER2 + MBC patients with distinct responses to trastuzumab using miRNA microarrays and constructed a four-miRNA signature to predict survival using a LASSO model [27].…”
Section: Discussionmentioning
confidence: 99%
“…Lasso has two important characteristics, one is feature selection: automatic selection of features, it will learn to remove features without information and precisely set the weights of these features to zero, especially for high-dimensional data. Another one is interpretability: models are easier to explain, for example, we can find the independent variables that provide the most important information in the model when we have a lot of independent variables [2326]. Li et al identified 13 differentially expressed miRNAs in the serum of HER2 + MBC patients with distinct responses to trastuzumab using miRNA microarrays and constructed a four-miRNA signature to predict survival using a LASSO model [27].…”
Section: Discussionmentioning
confidence: 99%
“…Значительная часть работ по использованию ИИ в трансплантологии посвящена решению проблем выживаемости и отторжения, главным образом у реципиентов почки или печени [21][22][23][24][25][26][27][28][29]. Другими важными задачами для решения методами машинного обучения являются подбор совместимых пар донора и реципиента [7,30], прогнозирование дисфункции трансплантата [31][32][33], а также подбор оптимального режима иммуносупрессии [8,34,35].…”
Section: искусственный интеллект в трансплантологииunclassified
“…The DEmRNAs were evaluated using univariate Cox'sproportional hazard regression model. Genes with P-value <0.05 were considered as candidate variables and entered into a stepwise LASSO regression [12][13][14][15] and multivariate Cox regression analysis.…”
Section: Survival Analysis and A Predictive Model For Prognosis Constmentioning
confidence: 99%